Functional and structural diversity in GH62 α‐L‐arabinofuranosidases from the thermophilic fungus Scytalidium thermophilum. Issue 3 (29th September 2014) - Kaur, Amrit Pal; Nocek, Boguslaw P.; Xu, Xiaohui; Lowden, Michael J.; Leyva, Juan Francisco; Stogios, Peter J.; Cui, Hong; Di Leo, Rosa; Powlowski, Justin; Tsang, Adrian; Savchenko, Alexei
Summary The genome of the thermophilic fungus Scytalidium thermophilum (strain CBS 625.91) harbours a wide range of genes involved in carbohydrate degradation, including three genes, abf62A, abf62B and abf62C, predicted to encode glycoside hydrolase family 62 (GH62) enzymes. Transcriptome analysis showed that only abf62A and abf62C are actively expressed during growth on diverse substrates including straws from barley, alfalfa, triticale and canola. The abf62A and abf62C genes were expressed in Escherichia coli and the resulting recombinant proteins were characterized. Calcium‐free crystal structures of Abf62C in apo and xylotriose bound forms were determined to 1.23 and 1.48 Å resolution respectively. Site‐directed mutagenesis confirmed Asp55, Asp171 and Glu230 as catalytic triad residues, and revealed the critical role of non‐catalytic residues Asp194, Trp229 and Tyr338 in positioning the scissile α‐L‐arabinofuranoside bond at the catalytic site. Further, the +2R substrate‐binding site residues Tyr168 and Asn339, as well as the +2NR residue Tyr226, are involved in accommodating long‐chain xylan polymers. Overall, our structural and functional analysis highlights characteristic differences between Abf62A and Abf62C, which represent divergent subgroups in the GH62 family.